*This preview shows
page 1. Sign up
to
view the full content.*

**Unformatted text preview: **r 2 +(3-α ) r-2( α-1) = ( r +2)( r-( α-1)). So the general solution is y ( t ) = C 1 e-2 t + C 2 e ( α-1) t . The e-2 t term goes to zero as t approaches inﬁnity, so we only need to concern ourselves with the second term. If α-1 < 0 (i.e. α < 1), then the solution will approach zero as t → ∞ . If α > 1 then the solution will become unbounded as t → ∞ (whether to positive or negative inﬁnity depends on C 2 ). 1...

View
Full
Document